Some Centrally Extended Derivations on Banach Algebras - Ick-Soon Chang; Jaiok Roh (Mathematics)
In this article, we consider centrally extended derivations on Banach algebras. We first establish the stability of centrally extended derivations on Banach algebras. Then, we prove that under some conditions, approximate centrally extended derivations on Banach algebras are linear CE derivations.